Syringomyelia in association with posterior fossa cysts. - Banna, M (American Journal of Neuroradiology, 1988)
This paper presents three patients with a triad of syringomyelia, midline posterior fossa cysts, and hydrocephalus. In the first patient, the clinical presentation was related to spinal cord cavitation, and the cranial anomalies were unexpected. In cases 2 and 3, the brain anomalies dominated the clinical picture, and syringomyelia was unexpected. These cases show that an examination of the whole neuraxis is as important in patients with midline posterior fossa cysts as it is in patients with developmental syringomyelia or Chiari I malformation.